The phenomenon of meeting the Prophet in this world: the Malay Sufi perception - Mohd Amin, Wan Mohd Azam (IIUM Press, 2011)
This paper examines the phenomenon of meeting the Prophet in this world. The analysis made on the authentic traditions and opinions of some of the traditionalists (muhaddith) reveals that the meeting with the Prophet can only take place in the true dream or al-ru'yah al-sadiqah as the Prophet who died long time ago will not return to this world. Contrary to this, one of the alleged sufi group of Malaysia develops the idea that the Prophet would return to this world by citing the views of outstanding scholars such as al-Suyuti (d.911/1505), al-Sha'rani (d.973/1565) and al-Dihlawi (d. 1176/1762). In-depth analysis on their arguments shows that they have applied a kind of reasoning technique on the Qur'anic verses and traditions and misquoted the opinions of famous scholars.